Life-threatening Dilated Cardiomyopathy Induced by Late-onset Neonatal Hypocalcemia - Po-Ching Chou; Lung-Chang Lin; Jong-Hau Hsu; Rei-Cheng Yang; Yuh-Jyh Jong; Zen-Kong Dai; Jiunn-Ren Wu (Elsevier, 2016)
Neonatal seizures caused by hypocalcemia may be associated with cardiopulmonary dysfunction and may require specific management other than calcium supplementation. Severe dilated cardiomyopathy is an extremely rare complication in neonatal hypocalcemia and often results in high morbidity and mortality. We report here a 14-day-old neonate presenting with a gradually increasing frequency of tonic seizures. After admission, arterial desaturation was found despite supplying oxygen (4 L/min) through nasal prongs and the patient developed life-threatening respiratory distress and heart failure secondary to dilated cardiomyopathy. His critical cardiopulmonary derangements rapidly improved after respiratory support, the administration of diuretic and inotropic drugs, and the correction of his hypocalcemia and hypomagnesemia. The patient responded to treatment and was well during the 1-year follow-up period. We present this unique case history of seizure, respiratory distress, and heart failure induced by transient hypocalcemia to remind clinicians about the importance of this rare, life-threatening, but reversible, disorder.